KAJIAN DAYA HAMBAT BAKTERI ASAM LAKTAT SILASE RANSUM KOMPLIT BERBASIS HASIL SAMPING JAGUNG, UBI KAYU DAN SAWIT - Anwar Efendi Harahap (State Islamic University of Sultan Syarif Kasim Riau, 2011)
Lactic acid bacteria as probiotic are considered alternative to antibiotic growth promotor. The aims of this study wereto investigate inhibition of lactic acid bacteria isolated from completed feed silage based on corn silage (SRKJ), palm silage(SRKS) and cassava silage (SRKU) by products. Data from Factorial Completely Randomized Design were analyzedvariance followed by Duncan test. The result showed that the inhibition and number lactic acid bacteria isolated from SRKJ(0,38 cm, 6,05 cfu/gr) were higher (P<0,05) than those of SRKS (0,27 cm, 5,82 cfu/gr) and SRKU (0,22 cm, 5,14 cfu/gr).It is concluded that lactic acid bacteria from SRKJ was the best in term of number latic acid bacteria and inhibition ability.